Solid oxide cell and solid oxide cell stack
By designing an electrolyte structure with a base, a dam and a recess in a solid oxide battery, and setting an air electrode in the recess of the electrolyte, the problem of the solid oxide battery being prone to rupture under pressure is solved, and its durability and performance are significantly improved.
Patent Information
- Application Number
- CN202380060440.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-01-31
- Filing Date
- 2023-07-24
- Publication Date
- 2025-04-25
AI Technical Summary
During assembly of the stacking structure or operating device of the solid oxide battery, pressure may cause the solid oxide battery to rupture or damage, resulting in insufficient durability.
A solid oxide battery is designed, which includes a fuel electrode, an electrolyte and an air electrode. The electrolyte consists of a base, a dam and a recess. The air electrode is arranged in the recess of the electrolyte. The region where the fuel electrode and the electrolyte overlap in the thickness direction of the electrolyte is greater than or equal to the region where the air electrode and the electrolyte overlap.
Through this structural design, the durability of the solid oxide battery is improved, and the pressure is concentrated on the air electrode is reduced, thereby reducing the possibility of rupture and damage and improving the performance of the battery.
Smart Images

Figure CN119895602A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a solid oxide cell and a solid oxide cell stack. Background Art
[0002] Solid oxide fuel cells (SOFC) and solid oxide electrolyzers (SOEC) include cells consisting of a solid electrolyte with an air electrode, a fuel electrode, and oxygen ion conductivity, and the cells may be referred to as solid oxide cells. Solid oxide cells generate electrical energy by electrochemical reactions, or generate hydrogen by electrolyzing water through the reverse reaction of solid oxide fuel cells. Compared with other types of water electrolysis cells or fuel cells (such as phosphoric acid fuel cells (PAFC), alkaline fuel cells (AFC), polymer electrolyte fuel cells (PEMFC), direct methanol fuel cells (DMFC)), solid oxide cells have low overvoltage based on low activation polarization, and have high efficiency due to low irreversible losses. In addition, because solid oxide cells can use not only hydrogen fuel, but also carbon fuel or hydrocarbon fuel, solid oxide cells can have a wide range of fuel selection, and because solid oxide cells have a high reaction rate in electrodes, solid oxide cells do not require expensive precious metals as electrode catalysts.
[0003] In the actual implementation of devices such as fuel cells and water electrolysis cells, a stack structure in which interconnectors and solid oxide cells are stacked on each other has been widely used. During the process of assembling the stack structure of solid oxide cells or operating the device, pressure may be applied to the solid oxide cells, which may cause the solid oxide cells to rupture or be damaged. Summary of the invention
[0004] Technical issues
[0005] An aspect of the present disclosure is to achieve a solid oxide cell having excellent durability and a solid oxide cell stack using the same.
[0006] Solution to the problem
[0007] In order to solve the above problems, according to one aspect of the present disclosure, a solid oxide cell includes: a fuel electrode; an electrolyte, including a base arranged on the fuel electrode, a dam arranged on the base, and a recess surrounded by the dam; and an air electrode, arranged in the recess of the electrolyte, wherein an area in which the fuel electrode and the electrolyte overlap with each other in a thickness direction of the electrolyte is greater than or equal to an area in which the air electrode and the electrolyte overlap with each other.
[0008] According to some example embodiments of the present disclosure, the air electrode may be spaced apart from the dam.
[0009] According to some example embodiments of the present disclosure, the base portion and the dam portion may form an integral structure.
[0010] According to some example embodiments of the present disclosure, the base portion and the dam portion may include different materials.
[0011] According to some example embodiments of the present disclosure, the base may include 8 mol % yttria-stabilized zirconia (8YSZ), and the dam may include 3 mol % yttria-stabilized zirconia (3YSZ).
[0012] According to an example embodiment of the present disclosure, the base may include a yttria-stabilized zirconia-based (YSZ-based) ion conductor, and the dam may include alumina.
[0013] According to some example embodiments of the present disclosure, the fuel electrode and the air electrode may have substantially the same width.
[0014] According to some example embodiments of the present disclosure, the fuel electrode may be wider than the air electrode.
[0015] According to some example embodiments of the present disclosure, the fuel electrode and the electrolyte may have substantially the same width.
[0016] According to some example embodiments of the present disclosure, a thickness of the dam may be less than or equal to a thickness of the air electrode.
[0017] According to another aspect of the present disclosure, a solid oxide cell stack includes: a first interconnector and a second interconnector; and a solid oxide cell arranged between the first interconnector and the second interconnector, wherein the solid oxide cell includes: a fuel electrode; an electrolyte including a base arranged on the fuel electrode, a dam arranged on the base, and a recess surrounded by the dam; and an air electrode arranged in the recess of the electrolyte, wherein an area where the fuel electrode and the electrolyte overlap with each other in a thickness direction of the electrolyte is greater than or equal to an area where the air electrode and the electrolyte overlap with each other.
[0018] According to some example embodiments of the present disclosure, the solid oxide cell stack may further include a sealing material disposed on an outer side of the solid oxide cell between the first interconnector and the second interconnector.
[0019] According to an example embodiment of the present disclosure, the sealing material may be in contact with the dam.
[0020] According to some example embodiments of the present disclosure, the sealing material may be in contact with an upper surface and an outer side surface of the dam.
[0021] According to some example embodiments of the present disclosure, the sealing material may be in contact with the upper surface, the outer side surface, and the inner side surface of the dam.
[0022] According to some example embodiments of the present disclosure, the air electrode may be spaced apart from the sealing material.
[0023] Advantageous Effects of the Invention
[0024] In the case of a solid oxide cell according to some example embodiments of the present disclosure, when the solid oxide cell is implemented in a stacked structure, the durability of the solid oxide cell can be improved. Therefore, the solid oxide cell can be used as a fuel cell or a water electrolysis cell, thereby improving the performance of the solid oxide cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is an exploded perspective view schematically showing a solid oxide cell according to an example embodiment of the present disclosure;
[0026] Figure 2 is a cross-sectional view of a region of a solid oxide cell;
[0027] Figure 3 is an enlarged view of the region of the fuel electrode;
[0028] Figure 4 is a magnified view of the electrolyte region;
[0029] Figure 5 is an enlarged view of the region of the air electrode;
[0030] Figure 6 is a diagram showing an example of forming a dam portion of an electrolyte;
[0031] Figure 7 is a diagram showing an example of forming a dam portion of an electrolyte;
[0032] Figure 8 is a cross-sectional view of a region of a solid oxide battery in a modified example;
[0033] Fig. 9 is a cross-sectional view of a region of a solid oxide battery in a modified example;
[0034] Fig.10 is a cross-sectional view schematically showing a solid oxide cell stack; and
[0035] Fig.11 is a cross-sectional view schematically showing a solid oxide cell stack. DETAILED DESCRIPTION
[0036] Hereinafter, the example embodiments of the present disclosure will be described with reference to specific example embodiments and the accompanying drawings. However, the example embodiments of the present disclosure may be illustrated in many different forms and should not be construed as being limited to the specific embodiments set forth herein. The example embodiments disclosed herein are provided to better explain the present disclosure to those skilled in the art. In the accompanying drawings, the shapes and sizes of the elements may be exaggerated for clarity, and the same reference numerals will always be used to represent the same or similar elements.
[0037] In order to clearly explain the present disclosure in the drawings, contents irrelevant to the description are omitted, the thickness of each component is magnified to clearly indicate multiple layers and regions, and the same reference numerals are used to describe components having the same functions within the scope of the same concept. Throughout the specification, unless otherwise specified, when a part "includes" or "contains" a component, this indicates that other components are not excluded and other components may be further included.
[0038] As used herein, the term "substantially the same width" means that the width may differ by a few percent (eg, 5% or less).
[0039] Figure 1 is an exploded perspective view schematically illustrating a solid oxide cell according to an example embodiment of the present disclosure. Figure 2 is a cross-sectional view of a region of a solid oxide cell. In addition, Figure 3 This is an enlarged view of the fuel electrode area. Figure 4 is a magnified view of the electrolyte region, Figure 5 is an enlarged view of the region of the air electrode.
[0040] Reference Figure 1 and Figure 2, the solid oxide cell 100 according to the exemplary embodiment of the present disclosure includes a fuel electrode 110, an electrolyte 120 and an air electrode 130, and the electrolyte 120 includes a base 121, a dam 122 and a recess 123. In addition, the area in which the fuel electrode 110 and the electrolyte 120 overlap each other in the thickness direction of the electrolyte 120 is greater than or equal to the area in which the air electrode 130 and the electrolyte 120 overlap each other. Since the electrolyte 120 includes the dam 122 and the air electrode 130 is disposed in the recess 123 of the electrolyte 120, the air electrode 130 can be effectively protected, thereby significantly reducing the possibility of cracks and damage to the air electrode 130. In addition, as will be described below, the solid oxide cell 100 can be applied in a stacked structure, thereby dispersing the pressure that can be applied to the fuel electrode 110 and the air electrode 130, and improving the air tightness of the solid oxide cell 100. In addition, these advantages can greatly contribute to improving the characteristics of the solid oxide cell 100. Hereinafter, the components of the solid oxide cell 100 are described in detail, and the case where the solid oxide cell 100 is used as a fuel cell is mainly described. However, the solid oxide cell 100 can also be used as a water electrolysis cell, and the opposite reaction to the case of the fuel cell will occur in the fuel electrode 110 and the air electrode 130 of the solid oxide cell 100.
[0041] Specifically, when the solid oxide cell 100 is used as a fuel cell, for example, water generation due to hydrogen oxidation or oxidation reaction of carbon compounds may occur in the fuel electrode 110, and oxygen ion generation reaction due to oxygen decomposition may occur in the air electrode 130. When the solid oxide cell 100 is used as a water electrolysis cell, a reaction opposite to that of the fuel cell may occur, for example, hydrogen may be generated by a reduction reaction of water in the fuel electrode 110, and oxygen may be generated in the air electrode 130. In addition, in the case of a fuel cell, a hydrogen decomposition (hydrogen ion generation) reaction may occur in the fuel electrode 110, and oxygen ions and hydrogen ions may be combined to generate water in the air electrode 130, and in the case of a water electrolysis cell, a water decomposition (hydrogen and oxygen ion generation) reaction may occur in the fuel electrode 110, and oxygen may be generated in the air electrode 130. In addition, in the electrolyte 120, ions may move toward the fuel electrode 110 or the air electrode 130.
[0042] The specific structures or materials of the fuel electrode 110, the electrolyte 120, and the air electrode 130 will be described. Figure 3, the fuel electrode 110 may include an electronic conductor 111 and an ion conductor 112, and the electronic conductor 111 and the ion conductor 112 may be a sintered body of particles. In addition, a hole H1 may be formed in the fuel electrode 110, and a gas, a fluid, etc. may enter and exit through the hole H1. The electronic conductor 111 may include a metal catalyst such as nickel (Ni), cobalt (Co), copper (Cu) or an alloy thereof, wherein the metal catalyst may be in a metallic state or an oxidized state. The ion conductor 112 of the fuel electrode 110 may include a ceramic phase, wherein the ceramic phase may include gadolinium oxide doped ceria (GDC), samarium oxide doped ceria (SDC), ytterbium oxide doped ceria (YDC), scandia stabilized zirconia (SSZ), and ytterbium oxide scandia stabilized zirconia (YbCSSZ).
[0043] The electrolyte 120 is provided on the fuel electrode 110. As an example of a material constituting the electrolyte 120, refer to Figure 4 , the electrolyte 120 may include an ion conductor 124, and a hole H2 may be formed in the electrolyte 120, through which a gas, a fluid, etc. may enter and exit. The ion conductor 124 may include a stabilized zirconia. Specifically, the ion conductor 124 of the electrolyte 120 may include scandia stabilized zirconia (SSZ), yttria stabilized zirconia (YSZ), scandia ceria stabilized zirconia (SCSZ), scandia ceria yttria stabilized zirconia (SCYSZ), or scandia ceria ytterbium stabilized zirconia (SCYbSZ).
[0044] Reference Figure 5 , the air electrode 130 may include an electronic conductor 131 and an ion conductor 132, and the electronic conductor 131 and the ion conductor 132 may be sintered bodies of particles. In the air electrode 130, the electronic conductor 131 may include a lanthanum strontium manganese (LSM)-based material, a lanthanum strontium cobalt (LSC)-based material, a lanthanum strontium cobalt manganese (LSCM)-based material, a lanthanum strontium cobalt ferrite (LSCF)-based material, a lanthanum strontium ferrite (LSF)-based material, a barium strontium cobalt iron (BSCF)-based material, or a samarium strontium cobalt (SSC)-based material. The ion conductor 132 may include a yttria-stabilized zirconia (YSZ)-based material, a cerium dioxide (CeO2)-based material, a bismuth oxide (Bi2O3)-based material, or a lanthanum gallate (LaGaO3)-based material. In addition, the air electrode 130 may be a porous body including pores H3, and gases, fluids, etc. may enter and exit through the pores H3.
[0045] To explain the dam structure of the electrolyte 120 in more detail, as described above, the electrolyte 120 includes the base 121, the dam 122, and the recess 123. The recess 123 is surrounded by the dam 122. That is, the recess 123 may be defined by the dam 122. However, in Figure 1In the embodiment of the present invention, the dam 122 blocks in all directions, and therefore, the recess 123 is not connected to the outside in the lateral direction, which is not necessary. That is, the dam 122 may include some discontinuous areas, and therefore, the recess 123 may be opened in the lateral direction through the discontinuous areas of the dam 122. The air electrode 130 may be disposed in the recess 123 of the electrolyte 120, and in this case, the air electrode 130 may be spaced apart from the dam 122 and disposed not to contact the dam 122. In the case where the air electrode 130 is not in contact with the dam 122 and is spaced apart from the dam 122, when pressure is applied to the solid oxide cell 100, the pressure may not be concentrated on the air electrode 130 and may be effectively dispersed toward the electrolyte 120. In addition, when the solid oxide cell 100 is implemented in a stacked structure, the gap between the interconnector and the solid oxide cell 100 may be reduced, and the contact area between the sealing material and the solid oxide cell 100 may be increased to improve its airtightness.
[0046] The dam 122 may be provided on the edge of the base 121 and may have an integral structure with the base 121. Here, the integral structure may mean a form in which the base 121 and the dam 122 are sintered together rather than being separately manufactured and attached. In the integral structure, a separate bonding layer may not be provided between the base 121 and the dam 122. In the case of a specific method of forming the dam 122, first, Figure 6 The structure shown may use a method in which the paste 121P for the dam portion is applied along the edge of the green sheet 121G for the base portion and sintered. Figure 7 As shown, a method of stacking a plurality of green sheets 121G and 122G may be used. In other words, this method corresponds to a method of forming a through hole T in the green sheet 122G for the dam, stacking the green sheet 122G on the green sheet 121G for the base, and then sintering the green sheets 121G and 122G.
[0047] In the electrolyte 120, the base 121 and the dam 122 may include the same material, but considering the respective functions of the base 121 and the dam 122, the base 121 and the dam 122 may include different materials. Specifically, the base 121 may include an ion conductor such as 8YSZ widely used as a material of the electrolyte 120, and the dam 122 may include 3YSZ having a strength higher than that of 8YSZ to enhance effects such as improved durability. In addition, as another example, the base 121 may include a YSZ-based ion conductor, and the dam 122 may include alumina (Al2O3). When the dam 122 includes alumina (Al2O3), the strength of the dam 122 may be excellent to improve the durability of the solid oxide cell 100.
[0048] In addition, if Figure 2As shown, the fuel electrode 110 and the air electrode 130 may have substantially the same width, and the solid oxide cell 100 may be implemented with a support structure of the electrolyte 120. Here, the widths of the fuel electrode 110 and the air electrode 130 may be measured in a direction perpendicular to the thickness direction (Z direction) of the electrolyte 120, and more specifically, the widths of the fuel electrode 110 and the air electrode 130 may be the widths measured in a ZY cross section disposed at the center of the solid oxide cell 100. In this case, in order to improve the accuracy of the width measurement, in addition to the center of the solid oxide cell 100, the ZY cross section may be obtained in other regions, and an average value of a plurality of width values may be used.
[0049] You can also use Figure 2 The exemplary embodiment of the present invention is in the form of an increase in the relative width of the fuel electrode 110. That is, as in Figure 8 In a modified example, the fuel electrode 110 may be wider than the air electrode 130, and further, the width of the fuel electrode 110 may be substantially equal to the width of the electrolyte 130. When the width of the fuel electrode 110 is extended in this manner, the solid oxide cell 100 may be implemented with a support structure of the fuel electrode 110. Figure 2 In the embodiment, the thickness of the dam portion 122 and the air electrode 130 are substantially the same as each other, but the relative thickness conditions of the dam portion 122 and the air electrode 130 may be changed to obtain the desired effect. Fig. 9 In a modified example, the thickness of the dam portion 122 may be smaller than the thickness of the air electrode 130 , and the thickness of the air electrode 130 may be sufficiently ensured to improve the reaction efficiency of the solid oxide cell 100 .
[0050] Hereinafter, a solid oxide cell stack 200 including the solid oxide cell 100 will be described. Fig.10 , the solid oxide cell stack 200 includes a first interconnect 201 and a second interconnect 202, and the solid oxide cell 100 having the aforementioned structure is disposed between the first interconnect 201 and the second interconnect 202. That is, the solid oxide cell 100 includes a fuel electrode 110, an electrolyte 120, and an air electrode 130, wherein the electrolyte 120 includes a base 121, a dam 122, and a recess 123. In addition, the area where the fuel electrode 110 and the electrolyte 120 overlap each other in the thickness direction of the electrolyte 120 is greater than or equal to the area where the air electrode 130 and the electrolyte 120 overlap each other.
[0051] The first interconnect 201 and the second interconnect 202 may be electrically connected to the solid oxide cell 100, and for example, when the solid oxide cell stack 200 includes a stacked structure of a plurality of solid oxide cells 100, the first interconnect 201 and the second interconnect 202 may be disposed between adjacent solid oxide cells 100 and may connect the solid oxide cells 100. The first interconnect 201 and the second interconnect 202 may have a flat plate structure and may include flow paths A1 and A2 through which gas may diffuse. The first interconnect 201 and the second interconnect 202 may include a material having excellent conductivity and low degradation in a high temperature environment. As a specific example, the first interconnect 201 and the second interconnect 202 may include a metal including stainless steel, nickel, iron, and copper. In addition, the first current collector 205 may be disposed between the first interconnect 201 and the fuel electrode 110, and the second current collector 206 may be disposed between the second interconnect 202 and the air electrode 130.
[0052] like Fig.10 and Fig.11 As shown, the solid oxide cell stack 200 may include a sealing material 204 disposed between the first interconnect 201 and the second interconnect 202 to connect the first interconnect 201 and the second interconnect 202. Here, the sealing material 204 may include a glass-based material, and in this case, the organization of the glass-based material becomes dense at high temperature to prevent liquid or gas leakage. In addition, as an additional sealing structure, the solid oxide cell stack 200 may also include a structure such as a gasket 203 disposed between the first interconnect 201 and the second interconnect 202, in which case the sealing material 204 may be disposed between the first interconnect 201 and the gasket 203 and between the second interconnect 202 and the gasket 203. The sealing material 204 may contact the dam 122, and specifically, the sealing material 204 may contact the upper surface and the outer surface of the dam 120. By adopting the dam 122, the contact area between the sealing material 204 and the solid oxide cell 100 may be increased compared to conventional technology, thereby improving the durability and airtightness of the solid oxide cell stack 200. In addition, the contact area between the sealing material 204 and the dam portion 122 can be further expanded, and as shown in FIG. Fig.11 As shown, the sealing material 204 may be in contact with the upper surface, the outer side surface, and the inner side surface of the dam portion 122. The contact area between the sealing material 204 and the electrolyte 120 may be sufficiently ensured, while the air electrode 130 may be spaced apart from the sealing material 204. With this structure, when the solid oxide battery stack 200 is assembled or driven, external influences such as stress applied to the air electrode 130 may be reduced to minimize performance degradation of the air electrode 130.
[0053] The present disclosure is not limited to the above-mentioned exemplary embodiments and the accompanying drawings, but is limited by the appended claims. Therefore, those of ordinary skill in the art may make various substitutions, modifications or changes without departing from the scope of the present disclosure defined by the appended claims, and these substitutions, modifications or changes should be interpreted as being included within the scope of the present disclosure.
Claims
1. A solid oxide battery comprising: Fuel electrode; an electrolyte including a base portion provided on the fuel electrode, a dam portion provided on an edge of the base portion, and a recessed portion surrounded by the dam portion; as well as an air electrode disposed in the recess of the electrolyte, wherein an area where the fuel electrode and the electrolyte overlap with each other in a thickness direction of the electrolyte is greater than or equal to an area where the air electrode and the electrolyte overlap with each other.
2. The solid oxide battery according to claim 1, wherein: The air electrode is spaced apart from the dam.
3. The solid oxide battery according to claim 1, wherein: The base and the dam are integral.
4. The solid oxide battery according to claim 1, wherein: The base and the dam include different materials.
5. The solid oxide battery according to claim 4, wherein: The base includes 8 mol % yttria stabilized zirconia (8YSZ), and the dam includes 3 mol % yttria stabilized zirconia (3YSZ).
6. The solid oxide battery according to claim 4, wherein: The base includes a yttria-stabilized zirconia-based (YSZ-based) ion conductor, and the dam includes alumina.
7. The solid oxide battery according to claim 1, wherein: The fuel electrode and the air electrode have substantially the same width.
8. The solid oxide battery according to claim 1, wherein: The fuel electrode is wider than the air electrode.
9. The solid oxide battery according to claim 1, wherein: The fuel electrode and the electrolyte have substantially the same width.
10. The solid oxide battery according to claim 1, wherein: The thickness of the dam portion is less than or equal to the thickness of the air electrode.
11. A solid oxide battery stack comprising: a first interconnect and a second interconnect; as well as a solid oxide cell disposed between the first interconnect and the second interconnect, Wherein, the solid oxide battery comprises: Fuel electrode; an electrolyte including a base provided on the fuel electrode, a dam provided on the base, and a recessed portion surrounded by the dam; and an air electrode disposed in the recess of the electrolyte, wherein an area where the fuel electrode and the electrolyte overlap with each other in a thickness direction of the electrolyte is greater than or equal to an area where the air electrode and the electrolyte overlap with each other.
12. The solid oxide battery stack according to claim 11, further comprising: A sealing material is disposed outside the solid oxide cell between the first interconnector and the second interconnector.
13. The solid oxide battery stack according to claim 12, wherein: The sealing material is in contact with the dam portion.
14. The solid oxide battery stack according to claim 13, wherein: The sealing material is in contact with an upper surface and an outer side surface of the dam portion.
15. The solid oxide battery stack according to claim 14, wherein: The sealing material is in contact with the upper surface, the outer side surface, and the inner side surface of the dam portion.
16. The solid oxide battery stack according to claim 12, wherein: The air electrode is spaced apart from the sealing material.
17. The solid oxide battery stack according to claim 11, wherein: Each of the first interconnect and the second interconnect includes a flow path through which a gas diffuses.